PENGARUH LOKASI MALL DAN TATA LETAK GERAI TERHADAP LOYALITAS TENANT DI DENPASAR - Yulianti, Ni Made Dhian Rani; Dwiya, Ketut Gede Sri (Universitas Pendidikan Nasional, 2018)
The influence of mall location and store lay out to tenant loyalty in Denpasar. The existence of tenants is one factor in the success of a mall. There are many factors that are considered by tenants before deciding to choose a Mall, some of which are the location and layout of the Mall. The decision to choose a business location and layout will lead to tenant loyalty to the Mall. The purpose of this research is to find out how the influence of location and layout on tenant loyalty through election decisions at a mall. The data used in this study is primary data through the distribution of questionnaires to 72 tenants. The data analysis technique used is path analysis (path analysis) with SmartPLS version 3.0.m3 software. The results of the study show that the location of the mall has no direct effect on the decision to choose the mall, while the layout has a direct effect. Decision variables have a direct and significant effect on loyalty. While the influence of location and layout variables on tenant loyalty is not significant, so it is true that the decision on business location selection as a full mediation variable. The Square Adjusted R value for the decision variable is only explained by 22.7% of the location and layout variables. Whereas the loyalty construct is only explained by 18.7% of the decision construct. The calculation results from Q Square can be seen that the value 0.108 is greater than 0, which means that the model has a good predictive relevance value. Keywords: Location, lay out, decision, loyalty